Broadening of Tax Base: Policy Challenges and the Way Forward - Ammar, Attiya (Journal of Public Policy Practitioners, 2023)
The developmental process in Pakistan has been hindered due to the large informal economy and insufficient tax compliance. Successive governments have failed to change the mindset due to flawed policies, administrative constraints, and rambling corruption. The gap in tax revenue is due to tax evasion and avoidance practices. The economy is constrained by individuals who fiddle with policies that affect both the society and the state. The core issues have been delineated along with the potential results. Qualitative research method has been employed to analyze the performance, challenges, and prospects of broadening the tax base. The findings of the study portray that although the implementation of tax policy aimed to broaden the tax base has improved considerably, however, simplifying tax codes and making them clearer can improve compliance, reduce errors, and make the system fairer. This can be achieved by minimizing exemptions, deductions, and loopholes. This policy could prove beneficial for stakeholders, particularly the policymakers, to formulate the future tax policy and strategies in order to obtain maximum tax revenue.